Transcription Pause and Escape in Neurodevelopmental Disorders - Eigenhuis, Kristel N.; Somsen, Hedda B.; van den Berg, Debbie L. C. (Frontiers in Neuroscience, 2022)
Transcription pause-release is an important, highly regulated step in the control of gene expression. Modulated by various factors, it enables signal integration and fine-tuning of transcriptional responses. Mutations in regulators of pause-release have been identified in a range of neurodevelopmental disorders that have several common features affecting multiple organ systems. This review summarizes current knowledge on this novel subclass of disorders, including an overview of clinical features, mechanistic details, and insight into the relevant neurodevelopmental processes.